The JOBS Act and mergers and acquisitions - Chu, Yongqiang; Liu, Ming; Zhang, Shu (Journal of Corporate Finance, 2022)
We examine how the Jumpstart Our Business Startup Act (JOBS Act) affects mergers and acquisitions. We find that U.S. private targets are valued higher after the JOBS Act relative to public targets acquired by U.S. acquirers. The announcement returns of acquirers who acquired U.S. private targets after the JOBS Act are lower. The effect concentrates on private targets that are unlikely to qualify as small reporting companies should they choose to go public. We also show that the results are unlikely to be driven by changes in deal synergy.